Agenda
039-0097-001 Basque Children's Committee. House of Commons June 7th, 1937. 3.30.p.m. AGENDA. 1. Minutes of last meeting 2. Business arising from the minutes (a) Appointment of additional Hon. Secretary. (b) Constitution of the Committee 3. Apologies for absence 4. Position with regard to evacuation and centres 5. Offer and appeal from Mr H.O. Leighton 6. Helpers 7. Any other business 8. Date of next meeting. 292/946/39/97